The effect of foreign ownership on trade receivables - Liem Nguyen (Cogent Business & Management)
There have been no studies examining the effect of foreign ownership on trade credit extension, while this specific type of investor is important in a developing country with a fledgling financial market. The present study provides the first empirical evidence on the link between foreign ownership and trade receivables, using a sample of 559 nonfinancial firms listed in Vietnam from 2010 to 2021. Employing the System Generalized Method of Moments estimator, we document a positive association between foreign ownership and trade receivables, suggesting the superiority of foreign investors in terms of management skill as well as more resources to facilitate the extension of trade credit. We check the robustness via Propensity Score Matching technique and 2SLS regression, and confirm the positive effect of foreign ownership. Furthermore, examining the role of trade credit extension in two groups with higher- and lower-than-median foreign ownership, we find that as firms have more foreign ownership, they reap more benefits (higher return on assets, better price-to-book value of equity, less bad trade receivables) from trade credit supply. Finally, we document that the interaction terms between foreign ownership and other variables have negative coefficients on trade credit supply, which brings several implications for working capital management.